A Preliminary Study of the Pseudo-Aristotelian Hermetica - Liana Saif (Columbia University Libraries, 2021)
The pseudo-Aristotelian Hermetica are an understudied yet influential group of texts surviving in Arabic that claim to record conversations between Aristotle and Alexander the Great. I propose a ninth-century dating for these texts on the basis of textual and contextual evidence. In them, Aristotle instructs Alexander on two major subjects to aid his royal pupil’s military career and personal life: the cosmos, the genesis of everything in it, and astral magic. This study provides a preliminary analysis of the texts’ manuscripts and content, discussing what makes them Aristotelian and Hermetic and highlighting the resonances of Zoroastrian astro-cosmogenic doctrines.